Superbroad near-infrared photoluminescence covering the second biological window achieved by bismuth-doped oxygen-deficient gadolinium oxide. Issue 82 (17th August 2016) - Zhang, Kai; Hou, Jing-Shan; Liu, Bo-Mei; Zhou, Yang; Yong, Zi-Jun; Li, Li-Na; Sun, Hong-Tao; Fang, Yong-Zheng
Abstract : We demonstrated that bismuth-doped oxygen-deficient gadolinium oxides, produced through a low-temperature topochemical reduction strategy using CaH2 as a solid-state reducing agent, show superbroad NIR PL covering the second biological window. Abstract : In this work, we demonstrated that bismuth-doped oxygen-deficient gadolinium oxides, produced through a low-temperature topochemical reduction strategy using CaH2 as a solid-state reducing agent, show superbroad near-infrared photoluminescence covering the second biological window. Structural analyses confirm that the topochemical reduction treatment of bismuth-doped gadolinium oxides creates oxygen vacancies in the gadolinium oxide matrix, which changes the coordination of Bi and makes it situate in a defective environment. Given the tantalizing superbroad near-infrared emission from the reduced phases, it is anticipated that this novel system may find applications for in vitro / in vivo near-infrared fluorescence imaging in the second biological window.